Sociodemographic Factors of Intercultural Intelligence and Competence (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The interdependence of people and the connection and networking are components of today's everyday business life. It is for this reason that communication plays a major role in all aspects of life, including in business. As physical boundaries are no longer an obstacle to successful business and distance can be overcome in just a few clicks on one of the smart devices, the need to master new skills is a necessity. Availability and work with colleagues, partners, people of other cultural assumptions and understanding of relationships and business require the existence of intercultural intelligence in everyone involved in the relationship. This paper aims to show which are the sociodemographic variables that influence, and to what extent, the intercultural competence of an individual.